CLINICAL PROFILE OF PATIENTS WITH HYDATID CYST AND MANAGEMENT AT A TERTIARY CARE CENTER - KAPIL RAMPAL; HARKANWALPREET KAUR; RIPANDEEP SINGH; SUDHIR KHICHY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: In this study, we aimed to assess the clinical profile of patients presenting to our surgical unit in the past 5 years, determined the risk factors associated with the disease, and also reviewed the management options. Methods: It is a retrospective observational study in which case records, from November 2017 to February 2024, were observed for age, gender, occupation, socioeconomic status, clinical features, radiological findings (size, site, number, status, and stage), serological test (enzyme-linked immunosorbent assay), mode of intervention, and a result of the intervention (complications – cysto-biliary fistula, allergic reaction, wound complications, duration of hospitalization, and death). Results: Of 33 patients studied, 42.42% of cases were from 31 to 40-year-old age group. 57.57% of cases were males. 60.6% of patients were from lower socioeconomic status. Pain abdomen was the most common symptom (84.8%) observed. Organomegaly was the most common (63.6%) sign recorded. Isolated splenic involvement was observed in 6% of cases. 51.6% of the liver hydatid cysts involved the right lobe of the liver and 12.9% had bilobar involvement. Eosinophilia was observed in 15.2% of cases. Raised alkaline phosphatase (63.63%) was the most common liver function test to be deranged. 75.8% of cases were managed with surgery. Conclusion: Hydatid disease is a neglected tropical disease and continues to be a significant public health matter in tropical and developing countries. A higher general awareness and education about the disease are vital to limit significant associated morbidity and mortality.